Network approaches for omics studies of neurodegenerative diseases - Zhao, Na; Quicksall, Zachary; Asmann, Yan W.; Ren, Yingxue (Frontiers in Genetics, 2022)
The recent methodological advances in multi-omics approaches, including genomic, transcriptomic, metabolomic, lipidomics, and proteomics, have revolutionized the research field by generating “big data” which greatly enhanced our understanding of the molecular complexity of the brain and disease states. Network approaches have been routinely applied to single-omics data to provide critical insight into the disease biology. Furthermore, multi-omics integration has emerged as a both a critical need and a new direction to connect the different layers of information underlying disease mechanisms. In this review article, we summarize popular network analytic approaches for both single-omics data and multi-omics integration, and discuss how these approaches have been utilized in studying neurodegenerative diseases.